Different interset rest intervals during the nordic hamstrings exercise in young male athletes - Drury, B.; Peacock, D.; Moran, J.; Cone, C.; Campillo, R. R. (Journal of Athletic Training, 2021)
Context: The Nordic hamstring exercise (NHE) is known to reduce hamstrings injury risk in athletes. To optimize the NHE, it is important to understand how acute resistance-training variables influence its performance. Objective: To examine the effects of different interset rest intervals (ISRIs) on force indices during performance of the NHE. Design: Crossover study. Setting: Laboratory. Patients or Other Participants: Ten well-trained, young, male, team-sport athletes (age = 20.7 ± 2.3 years, height = 179.4 ± 5.5 cm, mass = 83.9 ± 12.4 kg). Intervention(s): Participants performed 2 sets of 6 repetitions of the NHE with either a 1- or 3-minute ISRI. All sets were performed using the NordBord. Main Outcomes Measure(s): Peak force (newtons), average force (newtons), percentage maintenance, and percentage decline were recorded for both the dominant and nondominant limbs, and interlimb force asymmetries (percentages) were calculated. Results: No interactions or main effects (P > .05) were present between conditions or sets for any variables. However, individual repetitions showed reductions (P< .05; effect size range = 0.58-1.28) in peak force from repetition 4 onward. Conclusions: Our findings suggest that a 1-minute ISRI was sufficient to maintain force-production qualities and interlimb asymmetries between sets during the NHE in well-trained athletes. Nonetheless, practitioners should be aware of the potentially large decrements in peak force production that may occur within the set.